Social Imaginaries About Lithium Mining in Puno, Peru - Vela, Enrique Rivera; Quispe, David Eleazar Barra; Yana, Julio Fitzgerald Zevallos; Bustinza, David Benjamín Antezana (Journal of Ecohumanism, 2024)
The discovery of a lithium deposit in the province of Carabaya, located in the department of Puno in Peru, and its probable exploitation in the coming years is creating expectations in the population of the towns involved, so the objective of the article is aimed at identifying the social imaginaries about the expectations that the exploitation of this mineral brings with it. The methodology applied was qualitative, as techniques for the construction of information, direct observation, semi-structured interviews and documentary review were used. The conclusions we reached reveal that the social imaginaries that have been built are different between authorities and the general population, while some authorities begin to express doubts about the existence of sufficient amounts of lithium, the population maintains greater expectations in its exploitation that would generate economic dynamism in the province and therefore in the region, and with it greater progress for the communities; however, they are also aware that this would generate discomfort due to the negative impacts that would be experienced and that it would affect the environment and livestock production.